Profile of adult patients hospitalized for asthma exacerbation - Kambouche, Faouzia; Medjane, Rabia (International Journal of Medicine, 2024)
A variable proportion of patients presenting to the emergency department (ED) with acute asthma require admission to hospital. Previous studies have identified select factors associated with admission following ED presentation .However, patients hospitalized for AEs are highly heterogeneous and remain largely unexplored.This review discusses current aspects on the pathogenesis and pathophysiology of acute severe asthma exacerbations and provides the current perspectives on the management of acute severe asthma attacks in the emergency department and the intensive care unit.